Inhibitory Effect of the Leaves of Rumex crispus L. on LPS-induced Nitric Oxide Production and the Expression of iNOS and COX-2 in Macrophages - Nam Kyung Im; Yeon Seop Jung; Jun Hyeok Choi; Mi Hee Yu; Gil Saeng Jeong (Natural product sciences, 2014)
In this study, the anti-inflammatory effects of ethanol extract of Rumex crispus L. and its fractions were investigated in RAW 264.7 macrophages. To evaluate the anti-inflammatory effects of extract, we studied nitric oxide (NO), prostaglandin E2 (PGE2), and tumor necrosis factor-alpha (TNF-a) levels in RAW 264.7 cells. The ethanol extract of R. crispus L. significantly decreased NO production and the levels of other inflammatory factors, such as PGE2 and TNF-a, in lipopolysaccharide (LPS)-stimulated macrophages in a dose-dependent manner. We also assessed the inducible nitric oxide synthase (iNOS) and the cyclooxygenase 2 (COX-2) protein expression by western blot. Ethyl acetate fraction of R. crispus L. had the strongest anti-inflammatory effect. These results suggest that ethyl acetate extract of R. crispus L. might be beneficial in the treatment of chronic inflammatory diseases. KCI Citation Count: 3